(untitled) (Bangladesh Journal of Botany, 2018)
The components of root exudates released from healthy and unhealthy black locust (Robinia pseudoacacia L.) root were determined by GC-MS. The results showed that the kinds and contents of root exudates released from Black Locust are different for healthy and unhealthy plants, so it may be evaluated whether the Black Locust plants are healthy or unhealthy by the root exudates. Healthy plants can release more kinds of exudates than unhealthy plants, especially the kinds of acids, alcohol and ester. There are 46 kinds of compounds in the healthy Black Locust, but only 24 kinds in the unhealthy Black Locust. Many compounds are released from healthy plant but not from unhealthy, while many kinds of compounds are released from unhealthy plant but not from healthy one.